Development and in-vitro evaluation of candy based medicated lollipops: a novel system of drug delivery - Rathod, Minakshi; Sul, Sandesh; Poharkar, Sachin; Pandhare, Yuvraj; Muneshwar, Monali (Journal of Drug Delivery and Therapeutics, 2018)
Lollipops or lozenges are defined as the flavored medicated dosage forms intended to be sucked and held in the mouth or pharynx containing one or more medicaments usually in the sweetened base. Lollipops are commonly used for the purpose of local or systemic effects through the buccal mucosa. Advantages of the lollipop as dosage forms include increase in bioavailability, reduction in dose size, gastric irritation and bypass first metabolism1. Lollipop is designed to improve patient compliance, acceptability, transportation etc2The lollipops were prepared by heating and congealing method in a candy based industry with sucrose base. All the formulations prepared were subjected to various physicochemical parameters like hardness, content uniformity, friability, weight variation etc. Thickness of lollipop ranges from 12-13.2 mm. The hardness of these lollipops ranges between 10-11.5 kg/cm... Results of in-vitro release profile indicated that formulation L3, L6, and L10 were the most promising formulations as the extent of drug release from this formulation was high as compare to other formulations up to 30 mins. The in vitro release of medicated lollipop of ambroxol hcl was found in the release of drug from the lollipop depends on the type and concentration of polymer used. As per all satisfactory evaluation parameters, the batch L3 is found to be optimized batch. The stability studies showed that there was no change in the formulation after 90 days. The medicated lollipops can provide an attractive alternative formulation in the treatment of mucolytics in pediatric patients. Keywords: Amboxol HCl, Lollipops, mucolytic and mucokinetics.